2014
DOI: 10.3164/jcbn.13-97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different products of peach (Prunus persica L. Batsch) from a variety developed in southern Brazil on oxidative stress and inflammatory parameters in vitro and ex vivo

Abstract: Antioxidant, anti-glycation and anti-inflammatory activities of fresh and conserved peach fruits (Prunus persica L. Batsch) were compared. Fresh peach pulps, peels, preserve peach pulps and the preserve syrup were prepared at equal concentrations. Rat liver, kidney and brain cortex tissue slices were pre-incubated with peach samples, subjected to oxidative stress with FeSO4 and hydrogen peroxide. Fresh peach pulps and peel conferred higher protection against cytotoxicity and oxidative stress than preserve peac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
9
0
3
Order By: Relevance
“…In addition, these properties have not been evaluated in guava byproducts containing seeds, its main residue. Regarding peach, its peel has been reported to exert a protective effect against liver cytotoxicity and oxidative stress in vitro and ex vivo, which was associated to its content of polyphenols and carotenoids (Gasparotto et al, 2014). The effect of these juice by-products on obesity-related hepatic steatosis has not been evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, these properties have not been evaluated in guava byproducts containing seeds, its main residue. Regarding peach, its peel has been reported to exert a protective effect against liver cytotoxicity and oxidative stress in vitro and ex vivo, which was associated to its content of polyphenols and carotenoids (Gasparotto et al, 2014). The effect of these juice by-products on obesity-related hepatic steatosis has not been evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…While TRAP indicates the quantity of antioxidants presents in the plant extracts, the TAR indicates their antioxidant effectiveness (Gasparotto et al, 2014). The study results on TRAP/TAR assays showed that the EAMC had a significant antioxidant capacity can be attributed to the total phenolic content.…”
Section: Discussionmentioning
confidence: 91%
“…This method is based on the quenching of luminol-enhanced chemiluminescence (CL) derived from the thermolysis of AAPH as the free radical source (Lissi et al, 1992;Gasparotto et al, 2014). The background CL was measured by adding 4 ml of AAPH (10 mM) dissolved in glycine buffer (0.1 M, pH 8.6) to a glass scintillation vial.…”
Section: Total Reactive Antioxidant Potential (Trap) and Total Antioxmentioning
confidence: 99%
“…epidemiological studies have suggested that phenolic compounds and carotenoid from peach pulps and peel decrease the risk of cardiac disorders, brain disorders and cancer because of their antioxidant and anti-inflammatory effect (58,59). In addition, P. persica flower extract suppressed inflammation in lPS-simulated macrophages (60).…”
Section: Discussionmentioning
confidence: 99%